PENGEMBANGAN PANDUAN PRAKTIKUM SPEKTROSKOPI PADA MATA KULIAH FISIKA MODERN - Dessiana Irma Yuanita; Hamdi Ahsan; Ketang Wiyono (Universitas Sriwijaya, 2015)
This study aims produces a spectroscopic laboratory manual of modern physics, which is valid and practical. This is the development research that uses 4D (four-D model) which is modified into a 3D stage. 4D development model that used includes the steps are defining (define), stage design (design) and stage of development (develop) combined with Tessmer formative evaluation phase which includes the step of self-evaluation, expert review, one-to-one and small group evaluation. laboratory manual based on criteria developed practical guides consisting of the title experiments, experimental purposes, the basic theory, tools and materials, experimental procedure, observation data, data analysis and conclusions. Spectroscopic laboratory manual with a simple tool modification has been success developed that divided into four trials that determine the Rydberg constant of the hydrogen atom, determine the energy transition Helium atom, and determines the wavelength of the optical spectrum and the determination of the frequency of the laser beam. Data collected through interviews, expert validation, observation and questionnaire responses of students. Results of the validation test of the three aspects of assessment validator average gain of 4.53 with the category of very valid and the results of the questionnaire responses of students gained an average percentage of 89.28% with a very practical category. The weakness in this study is the lack of prior knowledge of students in using Matlab software and the limitations of the tool so that the pilot phase of respondents using practical tools alternately on each trial. aboratory manual that have been developed can be used by the student in the learning activities by using practical methods, especially in the matter of atomic theories of modern physics course.